A school for insecticides - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Lamine Sidibé, head of agricultural promotion in Beyla, Guinea, is involved in research on insecticide plants to protect crops against predators and disease. He asks himself 'Why don t we have at least one ACP agricultural research institute...